Peran filsafat memandang etika ilmu terhadap lifestyle dan normalisasi medsos - Azzahrani, Khafidhotun Nafisa; Pertiwi, Palupi Wira; Az-zuhri, Muhammad Rizqi Nazaruddin (Maliki Interdisciplinary Journal, 2026)
This article discusses the role of philosophy in examining the ethics of science toward lifestyle phenomena and the normalization of social media in the digital era. The rapid development of technology and social media has significantly transformed people’s lifestyles, especially among younger generations who consider social media an inseparable part of daily life. Digital platforms such as Instagram, TikTok, and YouTube not only facilitate communication and access to information but also influence identity formation, lifestyles, and individual ways of thinking. Phenomena such as Fear of Missing Out (FoMO), social media dependency, and shifts in social values have become important ethical and philosophical issues. In this context, philosophy and the ethics of science function as moral foundations for evaluating the use of social media so that it remains aligned with human values, social responsibility, and self-awareness. Through epistemological, ontological, and axiological approaches, individuals are encouraged to think critically in filtering information, understanding the nature of social media, and determining its values and benefits. Furthermore, self-awareness and moral control are essential in maintaining balance between real life and digital life. Therefore, philosophy provides a reflective and ethical framework for addressing the challenges of social media normalization in modern society.